The Calling of the Church in Times of Polarization - Zorgdrager, Heleen E.; Vos, Pieter (Brill, 2022)
In many societies all over the world, an increasing polarization between contrasting groups can be observed. Polarization arises when a fear born of difference turns into 'us-versus-them' thinking and rules out any form of compromise. This volume addresses polarizations within societies as well as within churches, and asks the question: given these dynamics, what may be the calling of the church? The authors offer new approaches to polarizing debates on topics such as racism, social justice, sexuality and gender, euthanasia, and ecology and agriculture in various contexts. They engage in profound theological and ecclesiological reflection, in particular from the Reformed tradition. Contributors to this volume are: Najib George Awad, Henk van den Belt, Nadine Bowers Du Toit, Jaeseung Cha, David Daniels, David Fergusson, Jan Jorrit Hasselaar, Jozef Hehanussa, Allan Janssen, Klaas-Willem de Jong, Viktória Kóczián, Philipp Pattberg, Louise Prideaux, Emanuel Gerrit Singgih, Peter-Ben Smit, Thandi Soko-de Jong, Wim van Vlastuin, Jan Dirk Wassenaar, Elizabeth Welch, Annemarieke van der Woude, and Heleen Zorgdrager.